Keberdayaan Petani Sayuran dalam Mengakses Informasi Pertanian di Sulawesi Selatan - Lukman Hakim; Basita Ginting Sugihen (Jurnal Penyuluhan, 2009)
Focus of this study is to research the capacity of crop farmers in improving their agribusiness by accessing agricultural information. The research objectives are to analyze the power of crop farmers in accessing relevant, accurate and timely information; and to analyze the relationship between accessing information, the level of empowerment of group farmers and the level of farmers productivity. This study was carried out at two districts Suchar Gowa and Enrekang at South Sulawesi Province. Primary data was collected from 240 respondents who are members of farmers group and their main activities are crop quowers. Quantitative analysis and qualitative descriptive analysis were employed to analyze the result of this study. The variables of this study are: relevance of information (X1); information accuracy (X2); timely manner of information (X3); the level of empowerment (Y1); and the level of farmers productivity (Y2).The capacity for farmers to access information was low. The capacity of farmers group and farmers productivity were low. The access of information had a significant relation with the level of group empowerment and the level of farmers productivity. Variables of the relevance of information and information accuracy have positive influence to the level of group capacity in accesing information. Variable of information accuracy have significant positive influence to the level of farmers productivity. Based on the relationship between variables in the model of farmers capacity to access agricultural information, it shows that variables of information accuracy and variables of task and group function were dominant and strategic factors related to farmers productivity. That means these indicators have significant role to improvement of farmers productivity.